Functional ventilatory alterations in adult patients with sickle cell disease - Andrés Pavel Peña Batista; Dianelis Perla Sierra Martínez; Julio Dámaso Fernández Águila; Maritza Cabrera Zamora; Reinaldo Pino Blanco; Flora Fernández Villares (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2020)
Foundation: in patients with sickle cell disease, lung function abnormalities are frequent and can be detected by spirometry. Objective: to describe the disturbances of the respiratory functions in patients with sickle cell disease followed in a provincial consultation of hemoglobinopathies. Methods: observational, descriptive, cross-sectional study. Seventy six patients, selected by accidental non-probabilistic sampling, of 88 adults followed at the Dr. Gustavo Aldereguía Lima Hospital were included. The variables studied were: age, sex, type of hemoglobinopathy, respiratory symptoms, history of acute thoracic syndrome, (clinical forms and number of events), comorbidities and ventilatory pattern. Functional ventilatory tests were performed with Hellige digital Microspiro. Results: the age group between 20-29 years was the most frequent (34.2%). There was a discrete female predominance (56.1%) and the SS genotype (67.1%). The most frequent of the respiratory symptoms was dyspnea and among the comorbidities heart failure in 9.2% of the patients. In 42.1% there was a history of acute chest syndrome, pneumonia in most cases. Nine patients (11.8%) presented obstructive disorders and 43 patients (56.6%) a restrictive pattern. In the SS genotype the risk of having spirometry alterations was three times higher than the rest [OR = 3.2 IC (1.7-5.9)] Conclusion: the finding of altered respiratory functional test with a predominance of the restrictive pattern was common. These modifications were observed more frequently in patients with the SS genotype.